Materiais híbridos multifuncionais: síntese, caracterização e aplicação na sorção de 17[alfa]-etilenoestradiol, amoxicilina e oxidação de sulfetos - Tatiana Aparecida Ribeiro dos Santos (2018)
In this work, hybrid materials, hydrophobized with the surfactantcetyltrimethylammonium bromide (CTA+Br-), were used for sorption of the antibiotic amoxicillin (AMX) and/or 17-ethinyl estradiol (EE) hormone. The obtained materials were characterized by thermal analysis (TG), atomic absorption in flames, adsorptiondesorption of N2 at 77 K, X-ray diffraction (XRD), scanning and transmission electron microscopy (SEM and TEM), spectroscopy infrared (IV), and positron-life spectroscopy(EVMP). The first hybrid material used was MCM-41 (Mobil Composition of Matter number 41) with CTA+Br- (M52CTA+). It was efficient for sorption of both AMX (55 mg g-1) and EE (15 mg g-1). Based on the study of isosteric heats and positron halflife spectroscopy data it was possible to propose that the removal of these contaminants occurs due to the sorption of these inside the MCM-41 tubes filled by the CTA+ micelles.The CTA+ modified clays were synthesized by the intercalation of different amounts of CTA+Br- between the lamellae of bentonite (BE) and vermiculite (VE). The materials were tested for the sorption capacity of EE, and it was found that clays without CTA+Brare not capable of sipping the hormone. The B16CTA+ material (bentonite with 16% CTA+Br-) presented higher sorption capacity when compared to the other solids of this series. The V16CTA+, V18CTA+ and V19CTA+ vermiculite samples showed similar EE sorption capacities. Finally, nitrogen-doped carbon nanomaterials were synthesized from ironimpregnated M52CTA+ material using acetonitrile as carbon and nitrogen source by CVD(Chemical Vapor Deposition) at 600, 650, 700 and 800 °C. The materials obtained showed an N/C ratio between 8.3-10.1% and a carbon content between 14-31%. Results of MET, TG, elemental analysis, Raman spectroscopy and XRD showed that the synthesis at higher temperatures led to the formation of larger amounts of carbon and nitrogen nanostructures and with carbon structures similar to bamboo. On the other hand, the results of XPS showed that the carbon structures obtained at 800 °C preferentially have the presence of less reactive nitrogen species (graphite nitrogen), while the materials obtained at 600 and 650 °C preferentially have more nitrogen groups reactive acids suchas pyridine. These materials were used as catalysts for the oxidation of sulphides. The type of nitrogen group present in the carbon structure directly influenced the activity of the materials. The catalysts obtained at lower temperatures had the best kinetics of sulphide oxidation, which was related to the presence of higher content of more reactivenitrogen groups.